2016
DOI: 10.1021/acs.jpcc.6b04360
|View full text |Cite
|
Sign up to set email alerts
|

Size-Specific, Dissociative Activation of Carbon Dioxide by Cobalt Cluster Anions

Abstract: The reaction of cobalt cluster anions Con (3 ≤ n ≤ 17) with CO2 was studied experimentally and theoretically to explore the size-specific activation mode of CO2 by Con. Mass spectrometric measurements revealed that the reactivity depends strongly on cluster size: the reactivity emerges abruptly at n = 7, peaks at n = 8–10, and then gradually decreases with increasing n. Infrared multiple photon dissociation spectra of ConCO2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…The infrared multiple-photon dissociation (IR-MPD) spectra presented in this report were recorded at the Fritz Haber Institute (FHI) in Berlin making use of the FHI free electron laser (FEL) 37 facility. The experimental setup has been described in detail previously 38,39 and only essential details are described here. Briefly, a rotating natural Pt target is ablated by a Nd:YAG laser (532 nm, 10 Hz).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The infrared multiple-photon dissociation (IR-MPD) spectra presented in this report were recorded at the Fritz Haber Institute (FHI) in Berlin making use of the FHI free electron laser (FEL) 37 facility. The experimental setup has been described in detail previously 38,39 and only essential details are described here. Briefly, a rotating natural Pt target is ablated by a Nd:YAG laser (532 nm, 10 Hz).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[19] Relevant to the studies here, CO2 was found to adsorb only on cobalt cluster anions Conwith n > 7, and a strong C=O stretching band around 1900 cm -1 signified dissociative binding. [20] The instrument and IR source used in these studies have been described previously. [20][21] Briefly, platinum cluster anions were generated by pulsed laser ablation of a 194 Pt isotopicallyenriched target.…”
mentioning
confidence: 99%
“…[20] The instrument and IR source used in these studies have been described previously. [20][21] Briefly, platinum cluster anions were generated by pulsed laser ablation of a 194 Pt isotopicallyenriched target. CO2 was introduced to a reaction channel downstream at ~30 °C and the resulting anionic cluster distribution was probed by reflectron time-of-flight mass spectrometry.…”
mentioning
confidence: 99%
“…Photoelectron spectroscopice xperiments revealed that the electronic charge was partly transferred to the Oa tom during the reaction. [47]…”
Section: Co 2 Activationmentioning
confidence: 99%
“…It was demonstrated by means of IRMPD spectroscopy that CO 2 was dissociatively activated on Co n − ( n =3–17) to form Co n (CO)O − , where the CO and O units are bonded to different sites of the cluster. Photoelectron spectroscopic experiments revealed that the electronic charge was partly transferred to the O atom during the reaction …”
Section: Co2 Activationmentioning
confidence: 99%